Proposing an Affective Literacy Framework for Young Learners of English in Malaysian Rural Areas: Its Key Dimensions and Challenges - Abdul Rahim, Fauziah; Lee, Seung Chun (Universiti Utara Malaysia Press, 2017)
Purpose - This study investigated rural English teachers perceptions of factors which influence the literacy development of young learners in rural school settings. This investigation led to a further enquiry on the dimensions of an affective literacy framework to support the English learning of rural young learners.